Logic, language, and computation : 9th International Tbilisi Symposium on Logic, Language, and Computation, TbiLLC 2011, Kutaisi, Georgia, September 26-30, 2011, Revised Selected Papers - Löbner, Sebastian; Marra, Vincenzo; Richter, Frank; Bezhanishvili, Guram (Lecture notes in computer science, 2013)
This book constitutes the refereed proceedings of the 9th International Tbilisi Symposium on Logic, Language, and Computation, TbiLLC 2011, held in Kutaisi, Georgia, in September 2011. The book consists of summaries of 3 tutorials presented at the symposium together with 13 full papers that were carefully reviewed and selected from the submissions. The papers are organized in two sections, one on Language and one on Logic and Computation. The range of topics covered in the Language section includes natural language syntax, semantics, and pragmatics, frames in natural language semantics, linguistic typology, and discourse phenomena. The papers in the Logic and Computation section cover such topics as constructive, modal, algebraic, and philosophical logic, as well as logics for computer science applications.